American Studies Program Vietnam - Quỹ Châu Á; Quỹ Châu Á
The Asia Foundation’s international relations program in Vietnam strengthens and improves U.S.-Vietnam relations by convening bilateral conferences, organizing research placements for visiting American and Vietnamese scholars, and supporting the development of Vietnamese Studies in the United States.